Use of neutropenic diet in the nutritional care of pediatric cancer patients with neutropenia: a scoping review - Ana Paula Carvalho Arnhold; Hana Gabriela Severino Araújo; Ana Facury Cruz; Mayla Cardoso Fernandes Toffolo; Silvia Fernandes Mauricio (Jornal de Pediatria, 2024)
Objective: to carry out a scoping review with the purpose of mapping the scientific evidence on the use of the neutropenic diet in neutropenic pediatric cancer patients. Source of data: The scoping review protocol was prepared in accordance with the PRISMA-ScR and the checklist before the literature search was performed. Articles on nutritional management in adults or on the treatment of other diseases, and articles that were not in Portuguese or English and published before the year 2000, were excluded. Data were extracted based on the Cochrane Consumer and Communication Review Group form. Summary of the findings: Three hundred and forty scientific articles were identified, with the final sample of this review consisting of nine studies. Although the neutropenic diet has been part of the nutritional management of pediatric cancer patients for more than 20 years, there is still great variation in the criteria for indicating use and starting and discontinuing it, as well as in the nutritional composition of the diet. Furthermore, there is no consensus on the impact of using a neutropenic diet on different clinical and nutritional outcomes. Conclusion: In the absence of guidelines that standardize the use of a neutropenic diet in pediatric patients with neutropenia, there are heterogeneous approaches reported in the literature, even within the same institution. The available literature presents an absence of evidence on the use, viability, and effectiveness of the neutropenic diet in oncological children with neutropenia. More studies are needed to identify the real impact of the neutropenic diet on clinical and nutritional outcomes.